Suppression and Rebound of Pallidal Beta Power: Observation Using a Chronic Sensing DBS Device - Cagle, Jackson N.; Wong, Joshua K.; Johnson, Kara A.; Foote, Kelly D.; Okun, Michael S.; de Hemptinne, Coralie (Frontiers in Human Neuroscience, 2021)
Pallidal deep brain stimulation (DBS) is an increasingly used therapy for Parkinson’s disease (PD). Here, we study the effect of DBS on pallidal oscillatory activity as well as on symptom severity in an individual with PD implanted with a new pulse generator (Medtronic Percept system) which facilitates chronic recording of local field potentials (LFP) through implanted DBS lead. Pallidal LFPs were recorded while delivering stimulation in a monopolar configuration using stepwise increments (0.5mA, every 20 seconds). At each stimulation amplitude, the power spectral density (PSD) was computed, and beta power (13-30Hz) was calculated and correlated with the degree of bradykinesia. Pallidal beta power was reduced when therapeutic stimulation was delivered. Beta power correlated to the severity of bradykinesia. Worsening of parkinsonism when excessive stimulation was applied was associated with a rebound in the beta band power. These preliminary results suggest that pallidal beta power might be used as an objective marker of the disease state in PD. The use of brain sensing from implanted neural interfaces may in the future facilitate clinical programming. Detection of rebound could help to optimize benefits and minimize worsening from overstimulation.